Optimization of Preventive Maintenance Planning for the Motor Cooling System at PLTGU Using Differential Evolution - Putranugraha, Derry; Garniwa, Iwa (International Journal of Electrical, Computer, and Biomedical Engineering, 2025)
Determination of the optimal preventive maintenance time of the three-phase induction motor (88WC) during operation at 380V in the cooling system of the Semarang Gas and Steam Power Plant (PLTGU) is done by combining the Power-Law Non-Homogeneous Poisson Process (NHPP) model and the Differential Evolution (DE) Algorithm to achieve minimum total maintenance cost. The parameters of NHPP, β = 1.75 and η = 7,198.99 hours, are estimated using the least squares method from the historical failure data for the 2020–2024 period, recording failures beyond 20,000 operating hours. The DE optimization results provide the optimum PM time of 371.60 hours to reduce the total cost from IDR 28,198,935 (for the 500-hour interval) to IDR 20,299,822, achieving a cost savings of 38%. Validation is performed using Monte Carlo simulations with 1,000,000 iterations that yield a pre-optimization failure probability of 0.56%. Sensitivity analysis using a ±20% parameter variation also proves the model's robustness. This data-driven framework is thus anticipated to increase the reliability and cost-effectiveness of the PLTGU cooling system and is scalable to other power-generating facilities